Ketergantungan merokok dan hubungannya dengan tingkat motivasi berhenti merokok pada sivitas akademika Universitas Riau - Elda Nazriati; Zulharman Zulharman; Bening Osia Suseno; Habiburrahman Habiburrahman (Universitas Syiah Kuala, 2020)
One of the success factors in quitting smoking is motivation. while smoking dependence makes quitting smoking more difficult. The purpose of this study was to determine whether smoking dependence was related to the motivation to quit smoking. A survey was conducted on 137 Riau University academicians who had or wre currently smokers. Samples were taken using side voluntaries. The smoking dependence questionnaire used the Fagerstrom Test for Cigarettes Dependence (FTCD) and the motivation to quit smoking from the Center for Tobacco Independence which was distributed online. The relationship between fagerstrom score and motivation to quit smoking was tested by means of the spearmen correlation test. research showed that most respondents were at a low level of smoking dependence with level 8 motivation (ready to quit smoking). There was a significant relationship in the opposite direction between smoking dependence and motivation to quit smoking